Reliability of Jacket-Type Structure Considering the Reserve Strength Ratio (RSR) - Brigitta Violyna El Tito; Rudi Walujo Prastianto; Daniel Mohammad Rosyid (International Journal of Marine Engineering Innovation and Research, 2024)
The projected demand for energy globally will continue to rise by 45% by 2030, with an average growth rate of about 1.6% per year. Oil and gas are estimated to fulfil about 80% of the world's energy needs. One facility that supports oil and gas exploitation is an offshore structure of the jacket-type platform. The challenge in building a jacket platform is the reliability of the structure. Offshore structures are designed to withstand extreme wave loads that can cause the collapse of individual components or the entire structure. This paper aims to analyze the reliability of the structure with the ultimate limit state. The author performs an ultimate strength analysis using the Nonlinear Pushover Analysis method to obtain the Reserve Strength Ratio (RSR) and a reliability analysis using the Monte Carlo Simulation (MCS) method. This analysis shows that the RSR minimum of 9.33 occurs with a 135° loading direction. The MCS results show that the Jacket platform has a high level of reliability of 0.99997, which fulfils the minimum required reliability for offshore structures.